Fibre optic sensors with biologically active coatings for the detection of cells. - Rendon Romero, Antonio (Cranfield University, 2019)
The purpose of this thesis is to develop a rapid, sensitive and selective optical sensor for Campylobacter jejuni detection as it is the most common cause of foodborne illness in humans. The optical sensor platform was based on the optical fibre long period grating (LPG). The LPG fabrication technique chosen was the point-by-point method, involving the UV irradiation of photosensitive doped optical fibre. This technique allows the tailoring of the sensor platform to the requirements of the application. Polyclonal antibodies were selected as the material which can selectively immobilise bacterial cells on to the surface of the fibre optic. Methodologies for reliable and repeatable coating of this material (antibodies) onto the surface of the sensor platform were developed. Two methods to integrate the antibodies to the surface of the fibre, adsorption and covalent binding, were explored. Bovine serum albumin was selected as the material to block the sites on the surface of the fibre not covered by the antibodies, with the aim to prevent non-specific adsorption. The sensor was tested in a direct assay using bacterial samples at different concentrations. The sensitivity of the sensor was evaluated using different concentrations of the target bacteria in a direct assay and multiple repetitions, achieving a limit of detection of 10⁴ and 10³ CFU/mL (colony-forming unit (CFU), a measure of viable cells in a sample) for the sensor created using adsorption and covalent binding of antibodies, respectively. The selectivity of the sensor was explored by testing the sensor against different bacteria in a direct assay and multiple repetitions. The response of the sensor was 100% for Campylobacter jejuni (target bacteria), 22.77% for Listeria monocytogenes, 9.47% for Salmonella typhimurium and 3.01% for Escherichia coli. The enhancement of the sensitivity of the sensor using cell staining was explored. Cell staining induces a change in the refractive index of the cell, enhancing the signal detected, improving the limit of detection by one order of magnitude to 10² CFU/mL.
Keywords: Campylobacter jejuni; detection; long period grating (LPG); optical fibre; irradiation; photosensitive